The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11027-022-10021-w
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to low-GWP alternatives with enhanced energy efficiency in cooling non-residential buildings of China

Abstract: The electricity demand for space cooling in the non-residential building (NRB) sector of China is growing significantly and is becoming increasingly critical with rapid economic development and mounting impacts of climate change. The growing demand for space cooling will increase global warming due to emissions of hydrofluorocarbons used in cooling equipment and carbon dioxide emissions from the mostly fossil fuel-based electricity currently powering space cooling. This study uses the Greenhouse Gas and Air Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…On the other hand, William et al [1], [12], [15] highlight that those buildings are responsible for consuming approximately 30.00% and 40.00% of global energy production, contributing to a considerable amount of greenhouse gas emissions, about 19.00%. Various strategies have been proposed in buildings to address this challenge, including energy, water, and material efficiency measures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, William et al [1], [12], [15] highlight that those buildings are responsible for consuming approximately 30.00% and 40.00% of global energy production, contributing to a considerable amount of greenhouse gas emissions, about 19.00%. Various strategies have been proposed in buildings to address this challenge, including energy, water, and material efficiency measures.…”
Section: Discussionmentioning
confidence: 99%
“…At the level of carbon emissions from buildings, excessive carbon emissions can lead to a sharp increase in greenhouse gases and waste of energy resources, which in turn can lead to building environmental problems such as the heat island effect. The issue of how to effectively reduce carbon emissions is critical to improving building performance [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. For example, the following scholars have conducted relevant studies: Zhang et al investigated the impact of three objectives, GWP, global cost (GC), and operational energy (OE), on the ability to optimize building performance.…”
Section: At the Building Gwp Levelmentioning
confidence: 99%
“…Wang et al examined the abatement potential of HFC emissions. The results indicated that the total GHG reduction capacity by 2050 is approximately equal to 10% of the total carbon emissions from the Chinese construction sector [24]. Honarvar et al examined the evolution of buildings over their life cycle, and the results showed that the environmental impact of new materials increases fivefold in terms of GWP.…”
Section: At the Building Gwp Levelmentioning
confidence: 99%